2009
DOI: 10.1007/s11426-009-0161-5
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of ferrocenyl imidazolines using bis(triphenyl)oxodiphosphonium trifluoromethanesulfonate

Abstract: An efficient synthesis of ferrocenyl imidazolines starting from ferrocenyl carboxylic acids has been developed. Bis(triphenyl)oxodiphosphonium trifluoromethanesulfonate was used to convert smoothly ferrocenyl carboxylic amides bearing an amine side chain, derived from ferrocenyl carboxylic acids and 1,2-diamines, to their corresponding ferrocenyl imidazolines. asymmetric catalysis, chiral, dehydration, ferrocene, imidazoline

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Wang et al reported the synthesis of ferrocenyl imidazolines (11) from ferrocenyl carboxylic acids (8) and enantiopure diamines (9) in high yields (Scheme 3). [27] These imidazoline derivatives had been commenced as ligands in transition metal-catalyzed processes. [28] The reaction was initiated by the formation of an intermediate amide (10) from the ferrocene containing carboxylic acid (8) and the diamine (9).…”
Section: Methods A: Synthesis Of Imidazolines From 12-diaminesmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al reported the synthesis of ferrocenyl imidazolines (11) from ferrocenyl carboxylic acids (8) and enantiopure diamines (9) in high yields (Scheme 3). [27] These imidazoline derivatives had been commenced as ligands in transition metal-catalyzed processes. [28] The reaction was initiated by the formation of an intermediate amide (10) from the ferrocene containing carboxylic acid (8) and the diamine (9).…”
Section: Methods A: Synthesis Of Imidazolines From 12-diaminesmentioning
confidence: 99%
“…Wang et al . reported the synthesis of ferrocenyl imidazolines ( 11 ) from ferrocenyl carboxylic acids ( 8 ) and enantiopure diamines ( 9 ) in high yields (Scheme ) . These imidazoline derivatives had been commenced as ligands in transition metal‐catalyzed processes .…”
Section: Synthesis Of Imidazolinesmentioning
confidence: 99%
“…Precursors 3aa – 3fc were obtained in good yields from the condensation of 2 with ( R )-BINDPCA 1a – 1e or 1f in the presence of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDCI) (1.0 mmol) and 1-hydroxybenzotriazole (1.5 mmol) in N , N -dimethylformamide (DMF). Then precatalysts 4aa – 4ab were synthesized from 3aa – 3ab through imidazoline formation using the Hendrickson’s reagent, while ligand L10 was obtained directly from 3fc in this way in moderate yield. After reduction of 4 with HSiCl 3 and Et 3 N in toluene under reflux, the desired ligands L1 – L9 could be obtained in moderate yields in two steps.…”
Section: Resultsmentioning
confidence: 99%
“…The hindered nature of amide 10 placed an unusual demand on Hendrickson’s phosphonium anhydride reagent for dehydrative cyclization. This reagent has performed well in numerous imidazoline syntheses, typically from less substituted diamine backbones. , Not surprisingly, initial attempts at ambient temperature in dichloromethane resulted in no conversion, and refluxing (40 °C) was similarly ineffective. Only when dichloroethane was used at reflux temperature (83 °C) did conversion occur.…”
mentioning
confidence: 99%